2021
DOI: 10.1039/d1ra05177f
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-modified heterogeneous Pd-catalyzed synthesis of acids, amides and esters from aryl halides using formic acid as the CO precursor

Abstract: To establish an environmentally friendly green chemical process, we minimized and resolved a significant proportion of waste and hazards associated with conventional organic acids and molecular gases, such as carbon monoxide (CO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Our preliminary attempt to synthesize DBDAPs via B–H amination and carbonylation was carried out in the presence of o -phenylenediamine ( 1a ) and 1,2-dibromobenzene ( 2 ) as model reactants using Pd(OAc) 2 in combination with t -BuXPhos (2-di- tert -butylphosphino-2',4',6'-triisopropyl-1,1'-biphenyl) (5 mol %), and Et 3 N (2.5 equiv) as base in DMF. In this case, DMF served as the CO surrogate, as it was disclosed that DMF, the reaction solvent, could act as a potential carbon monoxide surrogate under certain circumstances, notably, in metal-catalyzed aminocarbonylation procedures [ 19 20 ]. Unfortunately, no DBDAP was obtained and we only observed the formation of intermediate 3a in 25% yield (entry 1, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary attempt to synthesize DBDAPs via B–H amination and carbonylation was carried out in the presence of o -phenylenediamine ( 1a ) and 1,2-dibromobenzene ( 2 ) as model reactants using Pd(OAc) 2 in combination with t -BuXPhos (2-di- tert -butylphosphino-2',4',6'-triisopropyl-1,1'-biphenyl) (5 mol %), and Et 3 N (2.5 equiv) as base in DMF. In this case, DMF served as the CO surrogate, as it was disclosed that DMF, the reaction solvent, could act as a potential carbon monoxide surrogate under certain circumstances, notably, in metal-catalyzed aminocarbonylation procedures [ 19 20 ]. Unfortunately, no DBDAP was obtained and we only observed the formation of intermediate 3a in 25% yield (entry 1, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…When the reaction was performed using Co 2 (CO) 8 (0.3 equiv) in the presence of DBU, the intermediate 3a was isolated in 35% yield, but again no DBDAP 4 was obtained (entry 8, Table 1 ). Formic acid, an effective CO surrogate [ 20 , 22 ], was also screened. The reaction was carried out in the presence of acetic anhydride (Ac 2 O) as an activator, but unfortunately, no DBDAP was obtained (entry 9, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the DMF served as the CO surrogate, as it was disclosed that DMF, the reaction solvent, could act as a potential carbon monoxide surrogate under certain circumstances, notably, in metal catalyzed amino carbonylation procedures. [15][16] Unfortunately, no DBDAP was obtained, we only observed the formation of intermediate (3) in 25% yield (entry 1, Table 1). Next, the same procedure was carried out in the presence of molybdenum hexacarbonyl (Mo(CO)6) (2 equiv.)…”
Section: I1 -One-pot Synthesis Of Dibenzodiazepinonesmentioning
confidence: 89%
“…Metal‐support interactions have resulted in significant advancements in the development of commercially viable organic compounds. On the other hand, modifying (doping) support materials and catalysts with alkali metals has previously been shown to induce a phenomenon, increase their binding properties, and significantly improve the overall catalytic performance of the catalyst [4,7] …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, modifying (doping) support materials and catalysts with alkali metals has previously been shown to induce a phenomenon, increase their binding properties, and significantly improve the overall catalytic performance of the catalyst. [4,7] Corma and coworkers demonstrated that this supported gold catalyst has the unique capacity to activate both a twostep, one-pot process to synthesize azo compounds from nitrobenzene through hydrogenation and the oxidative coupling of anilines to azobenzenes. [8] In the following years, Pd or Pt nanowires in the presence of KOH, [9] Au/ZrO 2 through a photocatalytic route, [10] and CuBr/pyridine [11] systems have all been investigated for this reaction.…”
Section: Introductionmentioning
confidence: 99%